2022
DOI: 10.1111/ijsa.12407
|View full text |Cite
|
Sign up to set email alerts
|

Understanding dark side personality at work: Distinguishing and reviewing nonlinear, interactive, differential, and reciprocal effects

Abstract: The topic of dark side personality at work has received considerable research attention over the past decade, and both qualitative and quantitative reviews of this field have already been published. To show the relevance of dark personality in the work context, existing reviews have typically focused on systematically discussing the different criteria that have been linked to dark traits (e.g., job performance, work attitudes, leadership emergence, etc.). In contrast, and complementing this earlier work, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 125 publications
0
2
0
1
Order By: Relevance
“…Moreover, previous studies found that Machiavellianism is positively related to counterproductive work behaviors and causes a range of undesirable work outcomes (Stoica, 2021;Wille et al, 2022;Elsawyet al, 2022;Barry, 2020;Younus et al, 2020). Additionally, Machiavellianism associated positively with burnout and its components (emotional exhaustion, depersonalization, and diminished personal accomplishment), and negatively with general job satisfaction, life satisfaction, ethical behaviors, organizational commitment, job satisfaction, whistleblowing actions which are beneficial for the organization to achieve its goals, workplace spirituality, Organizational Trust Grover & Furnham, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies found that Machiavellianism is positively related to counterproductive work behaviors and causes a range of undesirable work outcomes (Stoica, 2021;Wille et al, 2022;Elsawyet al, 2022;Barry, 2020;Younus et al, 2020). Additionally, Machiavellianism associated positively with burnout and its components (emotional exhaustion, depersonalization, and diminished personal accomplishment), and negatively with general job satisfaction, life satisfaction, ethical behaviors, organizational commitment, job satisfaction, whistleblowing actions which are beneficial for the organization to achieve its goals, workplace spirituality, Organizational Trust Grover & Furnham, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Entre las causas de la aparición de estos liderazgos destacan determinados factores personales, como los propios rasgos de personalidad negativa de los líderes (la "dark personality", estudiada por Hogan y Hogan (2001) con su Manual diagnóstico y estadístico de trastornos mentales IV (DMS-IV) y por la perspectiva de la triada oscura o "dark triad" introducida por Paulhus y Williams (2002) (Wille et al, 2023)) -y la de los seguidores, predisponiéndolos a participar en estos procesos de manera activa. Otros estudios han explorado la importancia del contexto en el surgimiento de estos estilos de liderazgo, señalando así factores situacionales del entorno interno y externo de las organizaciones -como la falta de mecanismos de control, la complejidad y dinamismo de la industria, la inestabilidad y percepciones de amenaza o los valores culturales dominantes (Thoroughgood et al, 2018).…”
Section: Marco Teóricounclassified
“…Importantly, systematic reviews of this literature (e.g., Woods et al, 2019) have indicated an exclusive focus on the so-called bright-side (e.g., Big Five) traits when investigating personality development in work-related contexts, which means that the development of dark-side traits such as narcissism in conjunction with work experiences is still poorly understood (Wille et al, 2023). Although there is by now substantial evidence that also narcissism continues to develop and change once adulthood is reached (Barlett & Barlett, 2015; Carlson & Gjerde, 2009; Chopik & Grimm, 2019; Foster et al, 2003; Grosz et al, 2019; Klimstra et al, 2020; Orth & Luciano, 2015; Roberts et al, 2010; Wetzel et al, 2020; Wille et al, 2019), scant research has explored the role of work-related experiences in this developmental process.…”
mentioning
confidence: 99%